Miniaturowe perspektywy urbanistyczno-krajoznawcze Karela Čapka - Skibska, Anna Maria (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2018)
Miniature urban-tourist perspectives of Karel Čapek – in the essay, I make an attempt to cast some light on the Czech writer’s affection for detail of which poetics wields a description of space discovered by the author of Hordubal during his European voyages. Derived from a concept of “small nation”, interpreted – on the contrary to Milan Kundera – in the spirit of affirmation, this affection is expressed by a specific rhetorical dialectics of litotes and hyperbole which generates a narrative about small and often one-time “memorials” to the places visited by Čapek.
Miniature urban-touristic perspectives of Karel Čapek
Keywords: detail; litotes; hyperbole; phenomenology of travel; miniature